Dicvertase potential for the treatment of osteoarthrosis in the geriatric practice - T. D. Gridneva; A. L. Dobrynina; M. B. Plotnikov; V. V. Oudut (Бюллетень сибирской медицины)
Complex treatment of aged and old patients ( n = 60) suffering from deforming osteoarthrosis complicated with reactive synovitis in combination with associated pathology of cardiovascular system is studied. Natural antioxidant dicvertase introduced by ultrasonic waves was used. Positive combined action of ultraphonophoresis by dicvertase was revealed which resulted in lowering pain syndrome, increasing motions range in the affected joint, normalizing of immunity status which allows to broaden indications for the treatment of these patients by lowering the risk of development of pathologic response of the organism on the treatment and facilitates lowering drug loading on patients.